Do betting advertisements contain attention strategies that may appeal to children? An interpretative content analysis - Pitt, H.; Thomas, S.; Bestman, A.; Randle, M.; Daube, Mike (Australian Health Promotion Association, 2018)
Issue addressed: Concerns have been raised about the expansion of sports betting marketing and the impact it may have on children's gambling attitudes and behaviours. This study aimed to investigate the content of Australian betting advertisements to identify if they contained specific attention strategies that have been identified by tobacco, alcohol and gambling researchers as having particular appeal to children. Methods: An interpretative content analysis of 91 advertisements from 11 corporate bookmakers was conducted. A search of specific attention strategies that may appeal to adults, but also have been demonstrated in the public health literature as having particular appeal for children was used to develop a coding framework. This framework was then applied to analyse the advertisements. Descriptive statistics were used to generate quantitative data and qualitative illustrations were used to provide examples of the strategies found within the advertisements. Results: On average there were 7.6 attention strategies found per advertisement. The most common attention strategies were music (n = 80), voiceovers (n = 79) and catchy slogans (n = 78). There were some attention strategies that related specifically to betting, such as technology, and risk-reducing promotions. Conclusion: This research has demonstrated that the content of betting advertisements contains attention strategies that, based on the research findings from other areas of public health, may have particular appeal for children. So what?: This research provides important evidence which could encourage researchers, regulators and policy makers to consider changes to current advertising regulations, to ensure children are protected from the potentially engaging and harmful attention strategies present in betting advertisements.